Ask and You May Receive: Senators' Strategies for Securing Particularistic Benefits. Issue 2 (4th May 2021) - Gelman, Jeremy
Abstract: How do congressional leaders efficiently distribute particularistic benefits? When allocating funding, they face a problem: they want to help the rank-and-file, but do not know what projects are most valuable to their colleagues. I argue that leaders use two strategies to ensure projects are allocated efficiently, namely they reliably fund members' top priorities and line items that cost them little bargaining capital. Doing so allows them to bank political goodwill while guaranteeing that the rank-and-file have politically valuable credit-claiming opportunities. By matching senators' confidential prioritized requests for two appropriations bills from the 1990s to legislative outcomes, I examine how Senate leaders distributed federal funding. My findings show that the two strategies I identify strongly predict how much of a request is funded. Moreover, priorities and low-cost requests are more strongly associated with project funding than other factors commonly identified in the distributive politics literature. These results shed new light on how leaders distribute favors in Congress as well as help explain mixed findings about both who receives particularistic benefits and their electoral consequences.